It's not yet dark [videorecording (DVD)] - Fenton, Frankie; Farrell, Colin, 1976- ([publisher not identified], 2018)
The story of Simon Fitzmaurice, an Irish filmmaker who suffers from amyotrophic lateral sclerosis.